2021
DOI: 10.1089/jamp.2020.1592
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Dosing Through the Salmeterol–Fluticasone Propionate Easyhaler for the Management of Asthma and Chronic Obstructive Pulmonary Disease: Robustness Analysis Across the Easyhaler Lifetime

Abstract: Background: Easyhaler (registered trademark by Orion Corporation) is a multidose dry powder inhaler (DPI) for the treatment of asthma and chronic obstructive pulmonary disease (COPD), designed to be simple and easy to use. Salmeterol-fluticasone propionate (S-F) Easyhaler (50/250 and 50/500 lg per dose), available in several European countries, provides combined inhaled corticosteroid and long-acting beta agonist therapy for the management of asthma and COPD. A requirement of the European Committee for Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…It has been demonstrated that salmeterol ( β 2 receptor agonist) has a significant dilating effect on the bronchi of patients [ 19 ]. The release of pulmonary mast cell mediators such as triene and histamine is the basis for improvement and remission of the patient's disease condition, while fluticasone propionate is one of the glucocorticoids with strong water- and fat-soluble properties [ 20 ]. It can have an anti-inflammatory effect on the patient's body and clinical studies have confirmed that it does not cause any adverse effects [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that salmeterol ( β 2 receptor agonist) has a significant dilating effect on the bronchi of patients [ 19 ]. The release of pulmonary mast cell mediators such as triene and histamine is the basis for improvement and remission of the patient's disease condition, while fluticasone propionate is one of the glucocorticoids with strong water- and fat-soluble properties [ 20 ]. It can have an anti-inflammatory effect on the patient's body and clinical studies have confirmed that it does not cause any adverse effects [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a very recently reported non-comparative in vitro assessment of the salmeterol–fluticasone propionate Easyhaler (50/250 or 50/500 μg per dose) [ 25 ], performance, as quantified by the delivered drug dose (DD) and fine-particle dose, remained consistent throughout the lifespan of the inhaler (60 doses) and was unaffected by simulated environmental stress. Drug delivery remained unchanged with or without dropping (DD ranging from 99 to 104% for salmeterol and from 95 to 103% for fluticasone, when setting the initial dose values to 100%), vibration (DD after test: 100–102% and 97–100% for salmeterol and fluticasone, respectively), exposure to moisture (DD after test: 98–102% and 98–107% for salmeterol and fluticasone, respectively) and freeze–thawing (DD after test: 100–101% and 99–101% for salmeterol and fluticasone, respectively).…”
Section: Technical and Theoretical Aspects Of Inhaler Devicesmentioning
confidence: 99%
“…W tabelach 1 i 2 przedstawiono wybrane parametry charakteryzujące DPI zawierające połącze-Tabela 1. Najważniejsze parametry charakteryzujące DPI zawierające połączenie wGKS z LABA oraz produkowane przez nie chmury aerozolowe leków (na podstawie [11][12][13][14][15][16][17][18][19][20][21][22][23][24]). Tabela 2.…”
unclassified